Front Cover: Simultaneous identification and estimation of glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid in de‐glycyrrhized Ayurvedic lipid‐based formulation of Glycyrrhiza glabra using dual wavelength reverse phase‐high‐performance liquid chromatography. Issue 10 (19th October 2020) - Kumbhalkar, Bhagyashri; Walunj, Tanhaji; Chavan, Sandeep; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand
Abstract : DOI: 10.1002/sscp.202000015 The cover picture shows development and optimization of a simple but sensitive RP‐HPLC with a short run time, for simultaneous estimation of glycyrrhizin, 18 β‐glycyrrhetinic acid and glabridin. Decoction of Glycyrrhiza glabra root/stolon was dispersed in cow's ghee and sesame oil, separately and the finished products were partitioned in methanol and hexane for re‐extracting the target compounds. The samples injected in a C18 column were eluted using acetonitrile, acidified with O ‐phosphoric acid, as a mobile phase. The study reveals de‐glycyrrhized lipid based formulations used in Ayurveda